Non-Random Samples as a Data Collection Tool in Qualitative Art-Related Studies - Eslam Y Khalefa; Sri Nurhayati Selian (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
ABSTRACT Non-random sampling as a tool in data collection has widely become a prominent issue in art-related phenomena and is more complicated than ever due to the heterogeneity of the study population. However, the foremost justification of this paper was the identification of several gaps of literatures in the selection of samples that usually lead to misunderstanding. This is because literatures mostly are not related to arts. The misunderstanding includes sample design and representative sample selected size determination. Nevertheless, there is a wide variety of techniques, different styles and trends that influence the field of contemporary art. Confusion is created when many researchers rely on a random sampling strategy that relies heavily on artists rather than works of art. The aim of this study is to explain how to select a representative sample of a heterogeneous population in art-related research. The investigation provided a new vision to select samples of artists, art works and art lovers. This study used an inductive approach through reading books, articles, newspapers, and opinions of philosophers and scholars in the field of research methodology. The most important result of this paper is that non-random sampling is better and more effective than random sampling strategy in art-related studies as it provides beneficial results for heterogeneous populations especially with regard to artists, works of art and art lovers. Sampel Tidak Acak sebagai Alat Pengumpulan Data dalam Studi Terkait Seni Kualitatif ABSTRAKPengambilan sampel tidak acak sebagai alat dalam pengumpulan data telah menjadi isu yang menonjol dalam fenomena yang berkaitan dengan seni dan lebih rumit dari sebelumnya dikarenakan heterogenitas populasi penelitian. Namun justifikasi utama dari makalah ini adalah identifikasi beberapa gap literatur dalam pemilihan sampel yang biasanya menimbulkan kesalahpahaman. Hal ini karena kebanyakan literatur tidak berkaitan dengan seni. Kesalahpahaman mencakup desain sampel dan penentuan ukuran sampel yang dipilih secara representatif. Namun demikian, ada berbagai macam teknik, gaya dan tren berbeda yang mempengaruhi bidang seni rupa kontemporer. Kebingungan tercipta ketika banyak peneliti mengandalkan strategi pengambilan sampel acak yang sangat bergantung pada seniman daripada karya seni. Tujuan dari penelitian ini adalah untuk menjelaskan bagaimana memilih sampel yang representatif dari populasi yang heterogen dalam penelitian yang terkait dengan seni. Investigasi memberikan visi baru untuk memilih sampel seniman, karya seni dan pecinta seni. Penelitian ini menggunakan pendekatan induktif melalui membaca buku, artikel, surat kabar, dan pendapat filsuf dan sarjana dalam bidang metodologi penelitian. Hasil terpenting dari makalah ini adalah pengambilan sampel tidak acak lebih baik dan lebih efektif daripada strategi pengambilan sampel secara acak dalam studi terkait seni karena memberikan hasil yang bermanfaat bagi populasi yang heterogen terutama yang berkaitan dengan seniman, karya seni dan pecinta seni.